NETWORK VS RHIZOME: ATTEMPT AT COMPARATIVE ANALYSIS - Myronova, Natalia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article examines and compares the concepts of network and rhizome, their structures, functions and meanings in different fields. The similarities and differences between these two models have been analyzed. The relevance of these concepts in the context of current technological, social and organizational developments has been highlighted. The perspectives for further research on the rhizome, which we consider as a prototype of the cognitive metaphor of the sociocultural reality of the Francophonie, are outlined in the context of its implication in the analysis of the polysystemic network of French cultural codes.____________References:• Buydens, (2005). Sahara, l'esthétique de Gilles Deleuze, Paris, Vrin.• Deleuze, & Guattari, F. (1980). Mille Plateaux, Paris, Éditions de Minuit.• Deleuze,(1968). Différence et Répétition, Paris, PUF.• Myronova,, Maksymova, A., Senchylo-Tatlilioglu, C., Kostyuchok, P. & Nastenko, S. (2024). Linguistic divergence in the context of globalization: an analysis of linguistic changes and its impact on cultural identity. AD ALTA: Journal of Interdisciplinary Research, 14/01-XLII, 129–134. https://www.magnanimitas.cz/ADALTA/140142/papers/A_25.pdf• Pinhas, (2001). Les larmes de Nietzsche : Deleuze et la musique. Paris, Flammarion.
Keywords: network, rhizome, structure, interconnection, decentralization, hierarchy, non-hierarchy, communication